The Utilization of Digital Media to Build a Connection between Local Wisdom and Globalization in Social Studies Learning in Grade 4 Elementary School Social Sciences - Geor, Gorius; Pinontoan, Marien; N.H Jacobus, Susan (Universitas Syiah Kuala, 2024)
Education at the elementary school level has an important role in shaping the basis of students' knowledge and character. Social Sciences (IPS) subjects in Indonesia aim to introduce social, cultural, and geographical concepts, as well as connect local knowledge with global dynamics. In the era of globalization, it is important to integrate local wisdom with global phenomena so that students can understand these two aspects in a balanced way. Digital media, with its ability to disseminate information quickly and widely, offers a potential solution in overcoming this challenge. This study aims to explore the use of digital media in social studies learning in grade 4 elementary school to build a connection between local wisdom and globalization, as well as to see how digital media can enrich students' learning experiences with local and global cultural contexts. This research uses a literature study approach, by collecting various secondary sources related to the use of digital media in education, especially in connecting local wisdom with globalization in social studies learning. Data is collected through searches for relevant articles, books, and research reports. The results of the study show that digital media such as digital scrapbooks, digital comics, e-story books, and multiplatform media are effective in introducing the values of local wisdom to students. In addition, digital media is also able to bridge local knowledge with a global context, providing a more interactive and relevant learning experience to the needs of the times.